(untitled) (Revista Contexto & Saúde, 2023)
Objective: To analyze the performance of adults with Multiple Sclerosis (MS) in cognitive screening and to observe the correlation between age and cognitive abilities. Methods: It is a descriptive, observational, transversal and quantitative research. It was performed with 27 individuals with a medical diagnosis of MS, 22 women, 5 men, aged between 20 and 60 years. Data collection was performed using three instruments: Montreal Cognitive Assessment (Moca); Battery Brief of cognitive screening; and a Personal Identification Protocol. Data analysis was performed quantitatively, descriptively and inferentially. The Mann-Whitney test and Spearman correlation were applied, with a significance of p<0.05. Results: Most participants had memory complaints and difficulties in subtraction and delayed recall tests. It was found that there was a negative correlation between age and performance in cognitive screening tests. Participants were divided into two groups according to the MOCA score and statistical differences were observed in incidental memory (p=0.049), immediate memory (p=0.019), delayed memory (p=0.007) , in clock design (p=0.037), in semantic verbal fluency (p=0.008), repetition of digits (p=0.006), in subtraction (p=0.026), language (p=0.001), phonemic verbal fluency (p= 0.05), abstraction (p=0.019), delayed recall (p<0.001) and in the total score of the MOCA (p<0.001). Conclusion: The older the patient with multiple sclerosis, the worse the cognitive functioning, especially memory and executive functions.